The Relationship between Physical Literacy Level and Physical Activity among Junior High School Students - Madyan Alfath; Yudy Hendrayana; Sufyar Mudjianto (Universitas Negeri Semarang, 2026)
Physical inactivity among adolescents has become an increasingly worrying problem, highlighting the importance of physical education in fostering lifelong active behavior through the development of physical literacy. This study examines the relationship between physical literacy and physical activity levels among junior high school students in the context of school based physical education. A quantitative correlational design was used, involving 60 eighth grade students from a public junior high school in Bandung, Indonesia, who were selected using total sampling techniques. Physical literacy was measured using a validated questionnaire covering motor skills, motivation, knowledge, and self confidence, while physical activity levels were measured using the Physical Activity Questionnaire for Adolescents (PAQ-A). The data were analyzed using Pearson's product moment correlation and simple linear regression, after testing for normality and linearity. The results of the analysis showed a positive and statistically significant relationship between physical literacy and physical activity levels (p = 0.006; B = 0.467), indicating that students with higher physical literacy tended to be more active in participating in physical activities. These findings highlight the important role of physical education in developing physical literacy, which in turn contributes to increased participation in physical activity among adolescents. Strengthening physical literacy through structured and meaningful physical education learning is therefore essential for promoting active and sustainable lifestyles among junior high school students.